Sexual Oppression in Doris Lessing’s The Golden Notebook - Rana Ali Mhoodar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The Golden Notebook for Doris Lessing encompasses a complicated sketch that is adopted to show the complexity of life as represented by its characters. However, the concept of this piece of fiction are concerned with oppressed and submissive women. In this novel, the patriarchy of capitalism is depicted, which is for women – by no means disadvantageous. The way people is portrayed by it, is distinguished by male-dominance. This society shows the way women able to show their identity within male-defined relations. According to this assumption, this article deals with the society’s standpoint according to feminism ideas, to locate the facades of sexual oppression and how female/ woman characters show their resistance to destabilize structure of oppression. The outcome argued that the sexuality is a notable façade of oppression. Here, women’s oppression and exploitation by male-dominance that shows discrimination against women as being inferior. In this novel, female characters must cope with a social and institutional form of burden. As a result, these oppressed women can make use of their power and their strife to gain self-identity. Such gains are achieved against the patriarchy of capitalism. The conclusion/ the outcome shows that Doris Lessing approves what has argued that sexuality is a façade of women’s oppression. However, Doris believes that this aspect of females’ lives can constitute a part of female power to destabilize the structures of oppression, which have been the main reason in weakening women’s personality.